1993
DOI: 10.1093/ije/22.6.1159
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Infection as a Risk Factor for the Development of Tuberculosis: A Case-Control Study in Tanzania

Abstract: A population-based case-control study was carried out in Mwanza Region, Tanzania, to determine the relative and population attributable risk of human immunodeficiency virus type 1 (HIV-1) infection for developing active tuberculosis. Cases were 441 consecutively diagnosed patients with tuberculosis (all types), aged 15-54 years. Controls were a representative population sample of 4161 people, drawn in a stratified cluster sample from urban areas, roadside settlements, and rural villages. HIV-1 infection was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Third, declining HIV burden and increasing coverage of anti-retroviral therapy in Tanzania might be influencing this risk analysis [100][101][102]. Studies in 1990s showed that about 30% of incident tuberculosis cases were attributable to HIV [103,104], but in our study the population attributable fraction (PAF) for HIV in prevalent tuberculosis cases was 3%, indicating that HIV may not be as strong driver of the tuberculosis prevalence in Tanzania as before.…”
Section: Health Care Services Received By Individuals With Presumptivmentioning
confidence: 52%
“…Third, declining HIV burden and increasing coverage of anti-retroviral therapy in Tanzania might be influencing this risk analysis [100][101][102]. Studies in 1990s showed that about 30% of incident tuberculosis cases were attributable to HIV [103,104], but in our study the population attributable fraction (PAF) for HIV in prevalent tuberculosis cases was 3%, indicating that HIV may not be as strong driver of the tuberculosis prevalence in Tanzania as before.…”
Section: Health Care Services Received By Individuals With Presumptivmentioning
confidence: 52%
“…Paired HIV prevalence data from patients with TB and general populations were obtained from previous publications, 10,42,43,[46][47][48][49][50][51]98,99 the US Centers for Disease Control and Prevention, 45,46 the HIV database kept by the US Census Bureau, 102 and UNAIDS. 36 Mostdatawerefromsub-Saharan Africa, as shown in Figure 2A and B.…”
Section: Estimates Of Regional Irrs For Tbmentioning
confidence: 99%
“…However, only a few reports with a small number of cases, describing dialysis patients with TB, have been proposed [6, 7, 8, 9, 10, 11]. Additionally, increased prevalence of HIV infection and ethnic factors, which were the risk factors of TB, renders the understanding of behavior of TB in dialysis patients more difficult [7, 12, 13]. In an attempt to find the incidence and characteristics of TB in dialysis patients, we collected all the cases of newly diagnosed TB and dialysis patients in Taiwan during 1997.…”
Section: Introductionmentioning
confidence: 99%